Robust mixed-mode chromatography method development using Analytical Quality by Design approach for analysis of selected drugs - Svrkota, Bojana; Krmar, Jovana; Protić, Ana; Otašević, Biljana (Archives of Pharmacy, 2022)
Mixed-Mode Liquid Chromatography (MMLC) includes several separation mechanisms in a single column, which is why MMLC can analyze compounds in a broad range of polarities and ionization potentials in a single run. Acclaim Mixed-Mode WCX-1 column with the ability to expose hydrophobic and weak cation exchange interactions was thus selected to analyse a challenging mixture of neutral and cationic forms: ergotamine, mecloxamine, camylofin, caffeine and propyphenazone, used as a fixed combination. MMLC method was developed in line with Analytical Quality by Design (AQbD) approach implying the scientifically-based understanding of process properties and risk-based management of the method life cycle. AQbD refers to pre-definition of the method’s Analytical Target Profile (ATP) by means of baseline separations within the shortest possible time, as well as definition of Critical Method Attributes (CMAs) as a measure of method quality and Critical Method Parameters (CMPs) affecting CMAs. Acetonitrile content, pH and acetate buffer concentration were selected as CMPs since retention mechanism expression in MMLC strongly depends on the mobile phase characteristics. The dependence of CMAs on CMPs was revealed following a face-centred central composition design plan of experiments and accompanying mathematical models, coefficients and standard error values. Design Space in which ATP is achieved with a high level of reliability (π = 90%), was determined by Monte Carlo simulations taking error distribution into account. Its margins pointed out to the working point that assures proper method robustness (pH 5.2, 90 mM acetate buffer solution and 48% (v/v) of acetonitrile).